Vaccinology: historical milestones, achievements and problems - Kalinichenko , Svitlana; Martynov, Artur; Minukhin , Valery; Kordon, Tetyana; Ovetchin, Petro (Annals of Mechnikov's Institute, 2025)
Vaccines are immunobiological preparations derived from bacteria, viruses, or their essential products. They are utilized to actively immunize humans and animals to prevent infectious diseases. The extensive application of vaccines facilitates the development of acquired active immunity against corresponding infections, which can cause infectious diseases and pandemic outbreaks. Consequently, in contemporary society, vaccination represents a principal strategy for epidemic prevention. Various technologies are employed in producing safe and highly effective vaccines, including inactivation, attenuation, nucleic acid production, utilization of viral vectors, production of viral subunits, and generation of viral particles. Nonetheless, despite the plethora of available methods, ongoing efforts within the scientific community are concentrated on developing highly competent and effective vaccines that are simultaneously hypoallergenic, immunogenic, and safe. This review article reflects on the historical progression of vaccine development. It elucidates modern vaccine production technologies as human life is safeguarded from various potential diseases, thereby underscoring a significant avenue of research.